SIPAK RAGO DALAM KARYA SENI GRAFIS - Budiman Budiman; Yofita Sandra (Serupa The Journal of Art Education, 2021)
The making of the final work of graphic art, this serigraphy technique is to visualize the uniqueness of the swallow, including the lifestyle and anatomy with serigraphy techniques using several color prints besides that it is also useful for pairing concepts and techniques for working in graphic arts. There are several stages in carrying out this final work including preparation, elaboration, synthesis, concept realization and completion stages. Thus, ten graphic art works that visualize the various uniqueness of swallow birds with the following titles: first "Tersesat", second "Lurus", third "Pulang", fourth "Keraguan", fifth "Sekawan", sixth "Romantis", seventh "Kelompok", the eighth "Bebas", the ninth "Berselisih" and ten "Hidup".Kata Kunci: Sipak Rago, permaianan anak nagari, Seni Grafis.